Clinical Study To Evaluate The Efficacy Of Punarnavadi-Kanamula Yoga (Hypothetical) In Hypothyroidism - Sharma, Hrishabh Datt; Sharma , Indumati (International Research Journal of Ayurveda & Yoga, 2021)
Today’s era is all about psycho-somatic diseases. These intimate affections of mind & fast moving society have disturbed the psychosomatic structure of human beings which has led to various disorders e.g. hypertension, diabetes, ulcerative colitis and various endocrine related abnormalities. Modern era is influencing both body & mind status of the individual. Pathogenesis of hypothyroidism according to the principles of Ayurveda, we find ourselves around the fact that it is basically related to Agni. Dhatwagni is effected adversely due to influence of malfunctioning Jhataragni formed in the pathology of disease hypothyroidism. Hypothyroidism is a metabolic disorder in its net result, there is nothing wrong in comparing with the “Agnimandhya” principle of Ayurveda.